Edukasi Trading Forex kepada Warga Kelurahan Kandri Kecamatan Gunungpati Kota Semarang - Wahyuningsih, Panca; Paramita, Patricia Dhiana; Adhi, Daniel Kartika; Luhgiatno, Luhgiatno; Prabowo, Janitra (STIE Pelita Nusantara, 2024)
The increasingly rapid development of technology and information has encouraged many changes in the investment that a person can make, because all these activities can be done virtually with the existence of the internet. Even though investment transactions are greatly assisted by the existence of existing technology, without a good understanding and broad insight into the chosen investment field and the risks that will be faced, it will be very risky to invest. Considering this, it is necessary to provide education, training and assistance for investors before investing, because having in-depth knowledge and insight is an absolute requirement that investors must understand. One of the investment instruments that is getting a lot of attention today is forex. Forex (foreign exchange) has the meaning of foreign currency transactions or in Indonesia it is better known as foreign exchange. Forex is a type of trading or transaction that trades one country's currency against another country's currency (currency pairs) involving the main money markets in the world for 24 hours continuously. Meanwhile, forex trading means the activity of buying and selling foreign currency which is usually carried out online. The aim of forex trading as an investment is to seek profits from the difference in sales figures made. Forex trading is a very profitable investment, with the increasingly rapid development of fintech, forex trading has become a popular type of investment that has high liquidity, so it is quite profitable. Starting from the desire to provide education to residents to avoid 'fraudulent investments', the community service team took the initiative to provide education about forex trading for residents in Kandri Village, Gunungpati District, Semarang. So far, based on observations, residents of Kandri Village are not very familiar with investing in forex, because education about forex trading has never been carried out at all in this sub-district. This forex trading educational activity aims to increase citizens' knowledge about things that potential investors need to consider before investing, especially in the field of forex trading. Keywords: investment, financial markets and capital markets and forex trading